Pedagogía para la patrimonialización del Himno Nacional Mexicano. “Aunque no lo vea ni lo escuche, lo tengo siempre metido en mi cabeza” - Sarah Corona Berkin (Les Cahiers ALHIM)
The theme of this article is the Mexican National Anthem as the episode of a history common to all Mexicans. I analyze the pedagogical methods for teaching the National Anthem from a very early age. I ask: Which are the first features of the National Anthem that children learn at school? How does early learning influence the appropriation of the Mexican National Anthem? What does the national anthem communicate according to the Mexican children? In a study with 115 children in Mexico, through interviews and drawings, it was found that 5 years old children guess in the National Anthem, the own and the foreign national membership; that their first approaches to the concept of Nation are through the National Anthem; and that the anthem is related to their everyday life and their emotional interests.